The biology and relationships of the ground woodpecker - Oatley, Terence Barry (My University, 1992)
Paterson's recognition concept of species predicts that new species arise as an incidental consequence of adaptation by small, isolated populations to a new environment. If this is so, species-wide characteristics, especially those of the species fertillzation system, should have evolved entirely in isolation and should relate strongly to the normal habitat of the species. The purpose of this study is to explore and test thid theory. The African Ground Woodpecker Geocolaptes olivaceus is the tool for this exploration. The first phase of the study documents aspects of ecology, behaviour and breeding biology of this little-studied bird; the second phase establishes its relationship to other African woodpeck- ers, and in the third phase a hypothetical account of a speciation event is presented. The Ground Woodpecker is the only terrestrial picid on the African continent and its distribution is confined to the subcontinent south of the Tropic of Capricorn, It is seldom found far from rocks and boulders; these provide the birds with resting and hiding places and display platforms. The birds excavate tunnels in earthen banks for roosting and nesting. (Abbreviation abstract)
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for 'the degree of Doctor of Philosophy.
Keywords: Woodpeckers -- Behavior -- South Africa; Woodpeckers -- Behavior; Birds -- Behavior; Species